STEM CELL–BASED MYOCARDIAL REGENERATION AFTER INFARCTION: MOLECULAR MECHANISMS, TRANSLATIONAL CHALLENGES, AND EMERGING BIOTECHNOLOGICAL INNOVATIONS - Amanda Abramowicz,; Maja Osuch,; Maciej Osuch,; Olga Tatarata,; Martyna Jaciubek,; Carmena Luty,; Anna Kiełboń,; Zuzanna Olga Reklewska,; Kornelia Domagała,; Magdalena Rumin, (International Journal of Innovative Technologies in Social Science, 2026)
Myocardial infarction (MI) remains a major global health burden, driving substantial healthcare costs and long-term societal impact due to progressive heart failure and reduced quality of life. Conventional therapies improve survival but do not restore lost myocardial tissue. Stem cell–based cardiac regeneration represents a disruptive biomedical innovation situated at the intersection of biotechnology, translational medicine, and health systems transformation. This review examines contemporary regenerative strategies—including mesenchymal stromal cells, induced pluripotent stem cells, and cardiac progenitor cells—with emphasis on their underlying molecular mechanisms and technological advancements. Particular attention is given to exosome engineering, gene-modified stem cells, biomaterial-assisted delivery systems, hydrogel scaffolds, and tissue-engineered cardiac patches. Evidence from preclinical and clinical studies indicates functional improvements mediated predominantly through paracrine signaling, angiogenic stimulation, and immunomodulatory regulation rather than direct cardiomyocyte replacement. However, technological scalability, manufacturing standardization under GMP conditions, safety concerns, regulatory frameworks, and cost-effectiveness remain critical barriers to widespread implementation. The integration of regenerative cardiology with bioengineering, nanotechnology, and precision medicine may enable more sustainable and accessible therapeutic models. By situating stem cell–based cardiac repair within a broader innovation ecosystem, this review highlights both the transformative potential and the systemic challenges associated with next-generation cardiovascular therapies.